The Mediating Role of Organizational Culture on the Relationship between Employee Performance and Antecedents in the Hotel Sector - Ali Alsheikh, Ghaith Abdul raheem; Abd Halim, Mutia Sobihah Binti; Alremawi, Maysoon Shafeeq Ahmad Alremawi; A Tambi, Abdul Malek Bin (Journal of Reviews on Global Economics, 2018)
Abstract: Hotel managers face more risks and complexity in their work environment compared to their manufacturing firms’ counterparts owing the unique service characteristic offered by hotels. The hotel managements’ budgetary participation and their leadership styles, commitment quality management practices (QMPs) in terms of communications can all assist them in tackling the uncertain and risky environment for better performance of jobs. This article defined and measured leadership style, organizational commitment, quality management practices (QMPs) and their impact on organizational performance, and examined the moderating role of organizational culture on the above relationship. The article conducted an analysis of the empirical studies and models that related leadership style, organizational commitment, quality management practices (QMPs), organizational culture and performance. It primarily aimed to illustrate the conceptualization, measurement and examination of the different concepts. Following the analysis of literature, the findings showed that leadership style, organizational commitment, quality management practices (QMPs) and organizational culture significantly effects various hotel processes, employees and performance. The article also provided a description of the various dimensions of the leadership style and it found that with committed employees with norms and values consistent to those of the organization, the performance of the hotels can increase towards achieving it goals. This article suggests that the balanced scorecard (BSC) be used as a tool to measure performance in the performance management system. It also suggests that future studies focus in this area to shed light on the nature and the ability of variables to influence hotel performance. Hotel management and leaders are suggested to form robust quality management practices within the hotels to enhance its overall performance.Â